Negative active material and preparation method thereof, negative pole piece and lithium ion battery
By adopting the structure of composite core material and cladding material in the negative electrode material, the problem of lithium ions easily growing lithium dendrites on the surface of the negative electrode material is solved, and more uniform lithium ion deposition and higher battery performance are achieved.
Patent Information
- Application Number
- CN202510124221.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-26
- Publication Date
- 2025-03-18
AI Technical Summary
Lithium ions tend to grow lithium dendrites on the surface of the negative electrode material, resulting in loss of electrode active substances and safety hazards.
A composite core material is employed, including a substrate material and a first material, the substrate material having a plurality of pores, the first material embedded on the pore wall of the substrate material and is coated with a cladding material. The nucleation overpotential of lithium on the first material is smaller than the nucleation overpotential of the cladding material, promoting the nucleation and deposition of lithium ions on the first material.
The generation of lithium dendrites on the surface of the negative electrode active material is reduced, the circulation performance is improved, and the energy density and circulation stability of the battery are improved.
Smart Images

Figure CN119650673A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the field of electrochemical technology, and in particular to a negative electrode active material and a preparation method thereof, a negative electrode sheet, and a lithium ion battery. Background Art
[0002] Negative electrode materials have an important influence on the energy density, cycle performance, charge and discharge rate, and low-temperature discharge performance of lithium-ion batteries. However, due to the uneven deposition of lithium ions, lithium dendrites are prone to grow on the surface of negative electrode materials. After multiple cycles, lithium dendrites are prone to fall off the electrode, resulting in loss of electrode active materials; moreover, if lithium dendrites continue to grow, they may penetrate the battery separator and contact the positive electrode, causing a short circuit in the battery and posing a safety hazard. Summary of the invention
[0003] One of the purposes of the present invention is to provide a negative electrode active material to solve the problem in the prior art that lithium ions are prone to grow lithium dendrites on the surface of the negative electrode material; the second purpose is to provide a method for preparing the negative electrode active material; the third purpose is to provide a negative electrode plate; and the fourth purpose is to provide a lithium ion battery.
[0004] In order to achieve the above object, the technical solution adopted by the present invention is as follows:
[0005] A negative electrode active material includes: a composite core material and a coating material. The composite core material includes a base material and a first material, the base material has a plurality of pores, and the first material is arranged on the pore walls of the base material. The coating material is coated on at least part of the outer surface of the composite core material. The nucleation overpotential of lithium on the first material is less than the nucleation overpotential of lithium on the coating material.
[0006] According to the above technical means, the base material can be used as the skeleton material of the composite core material. The base material has multiple pore structures, which can provide more space for the insertion and extraction of lithium ions, and also help to alleviate the volume change during the charge and discharge process. On the one hand, the first material is embedded in the pore walls of the base material, so that the first material can directly participate in the deposition process of lithium ions. The nucleation overpotential of lithium on the first material is smaller than the nucleation overpotential on the coating material, so that lithium ions are more inclined to nucleate and deposit on the first material, which helps to induce lithium ions to deposit on the first material to reduce the formation of lithium dendrites on the surface of the negative electrode active material. On the other hand, the coating material can provide an isolation effect, which can prevent the composite core material from directly contacting the electrolyte, thereby reducing the probability of side reactions between metallic lithium and the electrolyte / electrolyte, and improving the cycle performance.
[0007] Furthermore, the particle size of the first material is smaller than the pore size of the base material, and the composite core material presents a porous structure.
[0008] According to the above technical means, the first material can be embedded in the pores and deposited on the pore walls of the base material; moreover, the smaller particle size of the first material makes the first material have a higher specific surface area, which helps to provide more active sites for lithium ion nucleation and deposition, so that the deposition of lithium ions on the first material will be more uniform and rapid, which helps to reduce the formation of lithium dendrites; and, in the case where the composite core material has a porous structure, the composite core material not only provides more space for the embedding and extraction of lithium ions, but also alleviates the volume change of the negative electrode material during the charge and discharge process; moreover, the porous structure can accommodate the precipitated metallic lithium and increase the accommodation space for lithium metal, so that the negative electrode active material can store and release more lithium ions during the charge and discharge process, so that the battery has a higher specific capacity.
[0009] Further, the first material includes silicon nanoparticles.
[0010] According to the above-mentioned technical means, silicon and lithium have a strong interaction force, and silicon nanoparticles can provide a large number of lithium-philic active sites, which are conducive to the uniform deposition and release of lithium ions in silicon nanoparticles, thereby reducing the formation of lithium dendrites; it also helps to reduce the stress concentration inside the silicon nanoparticles, thereby delaying the pulverization and shedding of the material and improving the cycle stability of the negative electrode active material.
[0011] Furthermore, the particle size of the silicon nanoparticles is less than or equal to 5 nm.
[0012] According to the above technical means, silicon nanoparticles can be more easily embedded into the pores of the base material and tightly attached to the pore walls to form a stable composite structure, thereby improving the stability of the composite core material; at the same time, the feasibility of the composite core material preparation process is also improved.
[0013] Furthermore, the silicon nanoparticles are amorphous silicon nanoparticles.
[0014] According to the above technical means, amorphous silicon nanoparticles can more easily penetrate into the pores of the base material due to their irregular shape and small particle size (≤5nm), which can improve the process feasibility of preparing the composite core material. Moreover, the silicon nanoparticles are dispersed in the pores of the base material and can also provide a large number of lithium-philic active sites.
[0015] Furthermore, in the Raman spectrum of amorphous silicon nanoparticles, at 400 cm -1 ~600cm -1 In the range, the characteristic peak of amorphous silicon is 480cm -1 The integrated area accounts for greater than or equal to 90%.
[0016] According to the above technical means, the content of crystalline silicon in amorphous silicon nanoparticles is low and the content of amorphous silicon is high, so that the particle size of the amorphous silicon nanoparticles can be made smaller.
[0017] Furthermore, the mass proportion of the first material in the negative electrode active material is in the range of 5% to 20%.
[0018] According to the above technical means, the mass proportion of the first material in the negative electrode active material can be within an appropriate range, the lithium deposition effect in the negative electrode active material can be improved, the formation of lithium dendrites can be reduced, and the negative electrode active material can have a higher lithium storage capacity.
[0019] Furthermore, the volume proportion of the first material in the negative electrode active material is in the range of 10% to 20%.
[0020] According to the above technical means, the volume proportion of the first material in the negative electrode active material can be within an appropriate range, the lithium deposition effect in the negative electrode active material can be improved, the formation of lithium dendrites can be reduced, the negative electrode active material can have a higher lithium storage capacity, and relatively more lithium metal accommodating space can be provided.
[0021] Further, the base material includes a carbon base material.
[0022] According to the above technical means, the porous structure of the carbon-based material provides an attachment site for the first material and increases the specific surface area of the negative electrode material, which is beneficial to the embedding and extraction of lithium ions; it also helps to alleviate the volume expansion of the first material during the charging and discharging process and improve the cycle stability of the negative electrode material.
[0023] Furthermore, the surface area of the substrate material ranges from 800 m 2 / g~2500m 2 / g.
[0024] According to the above technical means, firstly, the negative electrode active material has more active sites, which helps to increase the contact area between the negative electrode and the electrolyte, thereby accelerating the electrochemical reaction rate and improving the battery's charge and discharge performance; secondly, it can provide more channels and pores, which is conducive to the rapid diffusion of lithium ions, reduce the internal resistance of the battery, and improve the battery's energy conversion efficiency. Thirdly, it can also provide more space to accommodate the volume change of the negative electrode material, thereby improving the stability of the negative electrode structure and extending the battery's cycle life.
[0025] Furthermore, the pore volume of the substrate material ranges from 0.6 cm 3 / g~2.0cm 3 / g.
[0026] According to the above technical means, on the basis of ensuring the structural stability of the base material, the base material can have a relatively large pore space, so that there is more space inside the negative electrode active material to accommodate lithium ions, which can improve the lithium storage capacity of the negative electrode material, thereby increasing the energy density of the battery; it can also provide sufficient buffer space for the volume change of the negative electrode active material during the charging and discharging process, reduce the stress concentration inside the material, maintain the integrity of the negative electrode structure, and thus improve the cycle stability of the battery.
[0027] Furthermore, the average pore diameter of the pores of the base material is in the range of 2.0 nm to 10.0 nm.
[0028] According to the above technical means, it is beneficial for the first material (such as silicon nanoparticles) to enter the pores and adhere to the inner walls of the pores to form a stable composite structure, thereby improving the stability of the composite core material; at the same time, it also improves the process feasibility when preparing the composite core material.
[0029] Furthermore, the volume proportion of the mesopores in the pores of the base material is greater than 60%.
[0030] According to the above technical means, the first material (for example, silicon nanoparticles with a particle size less than 5nm) can enter the pores more easily and adhere to the inner walls of the pores to form a stable composite structure, thereby improving the stability of the composite core material; at the same time, it also improves the process feasibility of preparing the composite core material.
[0031] Further, the coating material includes a fluorocarbon compound.
[0032] According to the above technical means, the deposition of lithium metal on the outer surface of the negative electrode active material can be suppressed to avoid the generation of lithium dendrites. Moreover, the fluorocarbon compound can isolate the lithium deposited in the pores of the base material from the electrolyte / electrolyte, which can greatly reduce the probability of side reactions between the metal lithium and the electrolyte / electrolyte, and further improve the cycle performance.
[0033] Furthermore, the ratio of the molar number of the fluorine element to the molar number of the carbon element in the coating material is greater than 0 and less than or equal to 1.
[0034] According to the above technical means, the coating material can effectively inhibit the formation of lithium dendrites and the uniform deposition of lithium, thereby improving the first coulombic efficiency of the negative electrode active material.
[0035] Furthermore, the coating material comprises an inner layer material and an outer layer material, the inner layer material is composed of carbon elements, and the outer layer material is composed of fluorocarbon compounds.
[0036] According to the above technical means, the lithium affinity effect of the first material can be ensured.
[0037] Furthermore, the content of fluorine in the outer layer material gradually increases in a direction away from the composite inner core material.
[0038] According to the above technical means, the composite core material can be effectively protected; and the interface stability of the outer layer material can be further improved, which helps to reduce the performance degradation of the battery during the charging and discharging process and improve the cycle life and safety of the battery.
[0039] Furthermore, in the X-ray photoelectron spectrum of the outer layer material, the peak position of the C1s electron binding energy ranges from 283.3 eV to 288.6 eV, and the peak position of the F1s electron binding energy ranges from 684 eV to 694 eV.
[0040] According to the above technical means, the outer layer material forms a relatively stable fluorocarbon compound layer.
[0041] Furthermore, the mass proportion of the coating material in the negative electrode active material is in the range of 2% to 12%.
[0042] According to the above technical means, a thicker and more stable LiF layer can be formed on the coating material, thereby more effectively protecting the composite core material, effectively inhibiting the formation of lithium dendrites and the uniform deposition of lithium, and effectively improving the performance of the negative electrode active material.
[0043] Furthermore, the Dv50 of the negative electrode active material is in the range of 4 μm to 25 μm.
[0044] According to the above technical means, the compaction density of the negative electrode active material can be optimized, the transmission efficiency of lithium ions can be improved, and the internal resistance can be reduced, thereby improving the cycle stability and service life of the battery.
[0045] Furthermore, the specific surface area of the negative electrode active material is in the range of 1.0 m 2 / g~4.5m 2 / g.
[0046] According to the above technical means, more lithium ion diffusion channels can be provided, which is conducive to the rapid insertion and extraction of lithium ions, thereby improving the electrochemical performance of the battery.
[0047] A method for preparing a negative electrode active material, comprising:
[0048] Forming a composite core material; the composite core material comprises a base material and a first material, the base material has a plurality of pores, and the first material is arranged on the pore walls of the pores of the base material;
[0049] The coating material is coated on at least a portion of the outer surface of the composite core material; wherein the nucleation overpotential of lithium on the first material is less than the nucleation overpotential of lithium on the coating material.
[0050] It can be understood that the beneficial effects that can be achieved by the method for preparing the negative electrode active material provided by the above embodiment of the present invention can refer to the beneficial effects of the negative electrode active material described above, and will not be repeated here.
[0051] Further, forming the composite core material includes: using a vapor deposition process and utilizing silicon source gas to form a first material on the pore walls of the pores of the base material.
[0052] Further, the silicon source gas includes at least one of tetrahydrosilane, disilane, tetrafluorosilane, silicon trichloride, chlorosilane, hexamethyldisilane, tris(trimethylsilyl)silane, methylvinyldichlorosilane, dimethylvinylchlorosilane, tetravinylsilane and vinyltrichlorosilane.
[0053] According to the above technical means, the silicon source gas is a precursor that provides silicon elements, which decomposes or reacts with other gases at high temperatures to generate silicon nanoparticles, which are deposited on the pore walls of the base material to form the desired first material. In the case where the silicon source gas includes the above silicon compound, only a small amount of silicon source gas is needed to form silicon nanoparticles, which greatly reduces the silicon load required for the deposition process, can significantly reduce the vapor deposition reaction time, and reduce material costs.
[0054] Furthermore, in the vapor deposition process for forming the composite core material, the deposition temperature ranges from 400°C to 1000°C.
[0055] According to the above technical means, silicon nanoparticles with smaller particle sizes can be generated, and the interaction between the base material and the silicon source gas can be enhanced, so that the silicon nanoparticles are more evenly deposited on the pore walls of the base material.
[0056] Furthermore, coating the coating material on at least part of the outer surface of the composite core material includes: using a vapor deposition process and a carbon source gas to form a carbon coating material on at least part of the outer surface of the composite core material, and using a fluorine-containing gas to fluorinate the carbon coating material.
[0057] Further, the carbon source gas includes a hydrocarbon material, and the hydrocarbon material includes at least one of methane, acetylene, propylene, propane, toluene, xylene and styrene.
[0058] Furthermore, the fluorine-containing gas includes at least one of fluorine gas, nitrogen trifluoride and chlorine trifluoride.
[0059] According to the above technical means, a carbon source gas is used as a precursor to form a carbon coating material on at least part of the outer surface of the composite core material through a vapor deposition process. After the carbon coating material is formed, a fluorine-containing gas is used to perform a fluorination treatment to obtain a fluorinated carbon coating material.
[0060] Furthermore, in the vapor deposition process for forming the carbon coating material, the deposition temperature ranges from 550°C to 1000°C.
[0061] According to the above technical means, a relatively uniform carbon layer (whose material is a carbon coating material) can be formed on at least a portion of the outer surface of the composite core material.
[0062] Furthermore, the treatment temperature of the fluorination treatment of the carbon coating material is in the range of 100°C to 600°C.
[0063] According to the above technical means, a fluorinated carbon coating material with a relatively uniform thickness can be formed on the carbon coating material.
[0064] A negative electrode plate comprises: a current collector; and a negative electrode material layer disposed on at least one surface of the current collector, wherein the material of the negative electrode material layer comprises the negative electrode active material of any embodiment of the present application.
[0065] It can be understood that the beneficial effects that can be achieved by the negative electrode plate provided above in the present invention can refer to the beneficial effects of the negative electrode active material mentioned above, and will not be repeated here.
[0066] A lithium-ion battery comprises: an electrolyte, a positive electrode sheet and a negative electrode sheet of any embodiment of the present application. The positive electrode sheet and the negative electrode sheet are arranged in the electrolyte.
[0067] It can be understood that the beneficial effects that can be achieved by the lithium-ion battery provided above in the present invention can refer to the beneficial effects of the negative electrode active material mentioned above, and will not be repeated here.
[0068] Beneficial effects of the present invention:
[0069] (1) The present invention embeds the first material into the pore walls of the base material so that the first material can directly participate in the deposition process of lithium ions. The nucleation overpotential of lithium on the first material is smaller than that on the coating material, so that lithium ions are more likely to nucleate and deposit on the first material, which helps to induce the deposition of lithium ions on the first material to reduce the formation of lithium dendrites on the surface of the negative electrode active material. In addition, the coating material can provide an isolation effect, which can prevent the composite core material from directly contacting the electrolyte, thereby reducing the probability of side reactions between metallic lithium and the electrolyte / electrolyte and improving the cycle performance.
[0070] (2) The present invention sets the particle size of the first material to be smaller than the pore size of the base material, so that the first material is embedded in the pores of the porous structure of the composite core material and deposited on the pore walls of the base material; moreover, the smaller particle size of the first material allows the first material to have a higher specific surface area, which helps to provide more active sites for lithium ion nucleation and deposition, so that the deposition of lithium ions on the first material will be more uniform and rapid, which helps to reduce the formation of lithium dendrites; and, in the case where the composite core material has a porous structure, the composite core material not only provides more space for the embedding and extraction of lithium ions, but also alleviates the volume change of the negative electrode material during the charge and discharge process; moreover, the porous structure can accommodate the precipitated metallic lithium, increase the accommodation space for lithium metal, so that the negative electrode active material can store and release more lithium ions during the charge and discharge process, so that the battery has a higher specific capacity.
[0071] (3) The present invention sets the mass proportion of the first material in the negative electrode active material to be in the range of 5% to 20%, so that the mass proportion of the first material in the negative electrode active material can be within an appropriate range, the lithium deposition effect in the negative electrode active material can be improved, the formation of lithium dendrites can be reduced, and the negative electrode active material can have a higher lithium storage capacity.
[0072] (4) The LiF generated by the fluorocarbon compound in the lithium insertion process of the present invention has lithium phobia, and the amorphous silicon deposited in the pores of the base material has lithium affinity after lithiation. By utilizing the different nucleation overpotentials of lithium on the surface of LiF and the surface of lithium-silicon alloy, lithium metal can be induced to preferentially nucleate and precipitate on the surface of lithium-silicon alloy, and lithium can be deposited in the pores of porous carbon, thereby avoiding the growth of lithium dendrites on the surface of material particles.
[0073] (5) The present invention sets the range of the ratio of the molar number of fluorine element to the molar number of carbon element in the fluorocarbon compound to be greater than 0 and less than or equal to 1, so that the coating material can effectively inhibit the formation of lithium dendrites and the uniform deposition of lithium, thereby improving the first coulombic efficiency of the negative electrode active material.
[0074] (6) The negative electrode active material of the present invention only needs to deposit a small amount of silicon nanoparticles as active sites, and the required silicon loading amount is greatly reduced, which can greatly reduce the amount of silane used and the vapor deposition reaction time, thereby reducing material costs. BRIEF DESCRIPTION OF THE DRAWINGS
[0075] Figure 1 A schematic diagram of a composite core material provided by the present invention;
[0076] Figure 2 The present invention provides a flow chart of a method for preparing a negative electrode active material.
[0077] Among them, 10 is a composite core material; 11 is a base material; 12 is a first material; 20 is a coating material; 21 is an inner layer material; and 22 is an outer layer material. DETAILED DESCRIPTION
[0078] The following will describe the embodiments of the present invention with reference to the accompanying drawings and preferred embodiments. Those skilled in the art can easily understand other advantages and effects of the present invention from the contents disclosed in this specification. The present invention can also be implemented or applied through other different specific embodiments, and the details in this specification can also be modified or changed in various ways based on different viewpoints and applications without departing from the spirit of the present invention. It should be understood that the preferred embodiments are only for illustrating the present invention, not for limiting the scope of protection of the present invention.
[0079] It should be noted that the illustrations provided in the following embodiments are only schematic illustrations of the basic concept of the present invention, and thus the drawings only show components related to the present invention rather than being drawn according to the number, shape and size of components in actual implementation. In actual implementation, the type, quantity and proportion of each component may be changed arbitrarily, and the component layout may also be more complicated.
[0080] In lithium-ion batteries, the positive electrode and the negative electrode are connected by an electrolyte to form a complete battery system. During the charge and discharge process, lithium ions migrate between the positive and negative electrodes to store and release electrical energy. At the same time, the lithium salt in the electrolyte provides ionic conductivity to ensure the normal operation of the lithium-ion battery.
[0081] This embodiment provides a lithium-ion battery, including: an electrolyte, a positive electrode sheet and a negative electrode sheet. The positive electrode sheet and the negative electrode sheet are arranged in the electrolyte.
[0082] The electrolyte is the medium for ions to migrate between the positive and negative electrodes. The positive electrode is the part of the lithium-ion battery where the oxidation reaction occurs, including active materials, conductive agents and binders.
[0083] The negative electrode is the part of the lithium-ion battery where the reduction reaction occurs, including active materials, conductive agents and binders.
[0084] This embodiment provides a negative electrode sheet, comprising: a current collector and a negative electrode material layer. The negative electrode material layer is disposed on at least one surface of the current collector, and the material of the negative electrode material layer includes a negative electrode active material.
[0085] The performance of negative electrode materials has a significant impact on the capacity, cycle life and safety of batteries. Currently, graphite negative electrode materials are commonly used in commercial lithium-ion battery negative electrodes, but the theoretical capacity of graphite negative electrode materials is relatively low (372mAh / g), which restricts the further improvement of lithium-ion battery energy density and cannot meet the demand for high energy density batteries.
[0086] Compared with graphite negative electrode materials, lithium metal negative electrode materials have the following advantages: high theoretical capacity (theoretical lithium storage capacity is as high as 3861mAh / g), the lowest lithium insertion potential, and high open circuit voltage can be obtained when applied to batteries. However, due to the uneven deposition of lithium ions, lithium dendrites are easy to grow on the surface. After multiple cycles, lithium dendrites fall off the electrode, resulting in loss of electrode active material. If lithium dendrites continue to grow, they will penetrate the diaphragm and contact the positive electrode, causing a short circuit in the lithium-ion battery, posing a safety hazard.
[0087] Based on this, this embodiment proposes a negative electrode active material, including: a composite core material 10 and a coating material 20. Figure 1 As shown, the composite core material 10 includes a base material 11 and a first material 12. The base material 11 has a plurality of pores, and the first material 12 is disposed on the pore walls of the base material 11. The coating material 20 is coated on at least part of the outer surface of the composite core material 10; wherein the nucleation overpotential of lithium on the first material 12 is less than the nucleation overpotential of lithium on the coating material 20.
[0088] The base material 11 can be used as the skeleton material of the composite core material 10. The base material 11 has a plurality of pore structures, which can provide more space for the insertion and extraction of lithium ions and help alleviate the volume change during the charge and discharge process.
[0089] On the one hand, the first material 12 is embedded in the pore walls of the base material 11, so that the first material 12 can directly participate in the deposition process of lithium ions. The nucleation overpotential of lithium on the first material 12 is smaller than that on the coating material 20, so that lithium ions are more inclined to nucleate and deposit on the first material 12, which helps to induce the deposition of lithium ions in the first material 12 to reduce the formation of lithium dendrites on the surface of the negative electrode active material. On the other hand, the coating material 20 can provide an isolation effect, which can prevent the composite core material 10 from directly contacting the electrolyte, thereby reducing the probability of side reactions between metal lithium and the electrolyte / electrolyte, and improving the cycle performance.
[0090] In this embodiment, the particle size of the first material 12 is smaller than the pore size of the base material 11 , and the composite core material 10 presents a porous structure.
[0091] It can be understood that by setting the particle size of the first material 12 smaller than the pore size of the base material 11, the first material 12 can be embedded in the pores and deposited on the pore walls of the base material 11; moreover, the smaller particle size of the first material 12 makes the first material 12 have a higher specific surface area, which helps to provide more active sites for lithium ion nucleation and deposition, so that the deposition of lithium ions on the first material 12 will be more uniform and rapid, which helps to reduce the formation of lithium dendrites; and, in the case where the composite core material 10 has a porous structure, the composite core material 10 not only provides more space for the embedding and extraction of lithium ions, but also alleviates the volume change of the negative electrode material during the charge and discharge process; moreover, the porous structure can accommodate the precipitated metallic lithium and increase the accommodation space for lithium metal, so that the negative electrode active material can store and release more lithium ions during the charge and discharge process, so that the battery has a higher specific capacity.
[0092] In this embodiment, the first material 12 includes silicon nanoparticles.
[0093] Understandably, the theoretical specific capacity of silicon is much higher than that of the traditional graphite negative electrode material mentioned above. Moreover, silicon nanoparticles have a shorter lithium ion diffusion path, which makes silicon nanoparticles have higher lithium affinity. That is to say, there is a strong interaction between silicon and lithium. Silicon nanoparticles can provide a large number of lithium-affinity active sites, which helps the uniform deposition and release of lithium ions in silicon nanoparticles, thereby reducing the formation of lithium dendrites; it also helps to reduce stress concentration inside silicon nanoparticles, thereby delaying the pulverization and shedding of the material and improving the cycle stability of the negative electrode active material.
[0094] In this embodiment, the particle size of the silicon nanoparticles is less than or equal to 5 nm.
[0095] Illustratively, the particle size of the silicon nanoparticles may be 5 nm, 4 nm, 3 nm, 2 nm, or 1 nm, etc., which is not limited here.
[0096] It can be understood that the above-mentioned setting can make it easier for silicon nanoparticles to embed into the pores of the base material 11 and tightly adhere to the pore walls, forming a stable composite structure, thereby improving the stability of the composite core material 10; at the same time, it also improves the feasibility of the preparation process of the composite core material 10.
[0097] In this embodiment, the silicon nanoparticles are amorphous silicon nanoparticles.
[0098] It can be understood that the amorphous silicon nanoparticles can more easily penetrate into the pores of the base material 11 due to their irregular morphology and small particle size (≤5 nm), which can improve the process feasibility of preparing the composite core material 10. Moreover, the silicon nanoparticles are dispersed in the pores of the base material 11, and can also provide a large number of lithium-philic active sites.
[0099] In this embodiment, in the Raman spectrum of amorphous silicon nanoparticles, at 400 cm -1 ~600cm -1 In the range, the characteristic peak of amorphous silicon is 480cm -1 The integrated area accounts for greater than or equal to 90%.
[0100] For example, in the test of the Raman characteristic peak area of the crystalline silicon, a 514.5 nm laser may be used as an excitation light source.
[0101] It is understandable that the particle size of amorphous silicon is smaller than that of crystalline silicon. -1 ~600cm -1 In the case where the peak area of the characteristic peak of amorphous silicon accounts for ≥90%, the content of crystalline silicon in the obtained silicon nanoparticles is lower and the content of amorphous silicon is higher, indicating that the content of amorphous silicon nanoparticles is higher and the particle size of silicon is smaller.
[0102] In this embodiment, the mass proportion of the first material 12 in the negative electrode active material is in the range of 5% to 20%.
[0103] For example, the mass proportion of the first material 12 in the negative electrode active material may be 5%, 7.5%, 10%, 15% or 20%, etc., which is not limited here.
[0104] It can be understood that when the mass proportion of the first material 12 in the negative electrode active material is small, it may lead to fewer lithium-philic active sites, resulting in insufficient improvement of the uniformity of lithium deposition by the first material 12, and affecting the effect of the first material 12 in reducing the formation of lithium dendrites. When the mass proportion of the first material 12 in the negative electrode active material is large, it may cause increased stress after lithiation, affecting the lithium-philic effect of the first material 12, and may also have a bad effect on the battery cycle performance. Moreover, since the gram capacity of metallic lithium (3861mAh / g) is higher than the gram capacity of silicon alloy lithium storage (3579mAh / g), when the mass proportion of the first material 12 in the negative electrode active material is large, it may reduce the content of metallic lithium in the negative electrode material during battery use, so that the lithium storage gram capacity of the negative electrode active material is low. Therefore, through the above-mentioned setting, the mass proportion of the first material 12 in the negative electrode active material can be within a suitable range, the lithium deposition effect in the negative electrode active material can be improved, the formation of lithium dendrites can be reduced, and the negative electrode active material can have a higher lithium storage gram capacity.
[0105] In this embodiment, the volume proportion of the first material 12 in the negative electrode active material is in the range of 10% to 20%.
[0106] For example, the volume proportion of the first material 12 in the negative electrode active material may be 10%, 12%, 14%, 16%, 18% or 20%, etc., which is not limited here.
[0107] It can be understood that when the volume proportion of the first material 12 in the negative electrode active material is small, it may lead to fewer lithium-philic active sites, resulting in insufficient effect of the first material 12 on improving the uniformity of lithium deposition, and affecting the effect of the first material 12 on reducing the formation of lithium dendrites. When the volume proportion of the first material 12 in the negative electrode active material is large, the pore volume of the composite core material 10 may be small, resulting in increased stress between particles of the first material 12 after lithium insertion and loss of lithium-philic effect. Moreover, when the volume proportion of the first material 12 in the negative electrode active material is large, lithium ions are mainly stored in the form of lithium-silicon alloy after insertion, which may reduce the gram capacity of the negative electrode active material. Therefore, through the above-mentioned settings, the volume proportion of the first material 12 in the negative electrode active material can be within an appropriate range, the lithium deposition effect in the negative electrode active material can be improved, the formation of lithium dendrites can be reduced, the negative electrode active material can have a higher lithium storage gram capacity, and provide relatively more lithium metal accommodating space.
[0108] In this embodiment, the base material 11 includes a carbon base material.
[0109] It can be understood that the carbon-based material has excellent conductivity, which can ensure the rapid transmission of electrons in the negative electrode active material, thereby improving the charge and discharge efficiency of the battery. The carbon-based material exhibits good chemical stability in the electrochemical environment, can resist the erosion of the electrolyte, and maintain the integrity of the negative electrode material structure. The porous structure of the carbon-based material provides an attachment site for the first material 12, and also increases the specific surface area of the negative electrode material, which is conducive to the insertion and extraction of lithium ions; it also helps to alleviate the volume expansion of the first material 12 during the charge and discharge process, and improves the cycle stability of the negative electrode material.
[0110] In this embodiment, the surface area of the base material 11 is in the range of 800 m 2 / g~2500m 2 / g.
[0111] For example, the surface area of the substrate material 11 may be 800 m 2 / g、1000m 2 / g、1500m 2 / g, 2000m 2 / g or 2500m 2 / g, etc. There is no limit here.
[0112] It can be understood that the surface area of the substrate material 11 is in the range of 800 m 2 / g to 2500m2 / g, the substrate material 11 has a relatively high specific surface area. On the one hand, it makes the negative electrode active material have more active sites, which helps to increase the contact area between the negative electrode and the electrolyte, thereby accelerating the electrochemical reaction rate and improving the charge and discharge performance of the battery; on the other hand, it can provide more channels and pores, which is conducive to the rapid diffusion of lithium ions, reduce the internal resistance of the battery, and improve the energy conversion efficiency of the battery. On the third hand, it can also provide more space to accommodate the volume change of the negative electrode material, thereby improving the stability of the negative electrode structure and extending the cycle life of the battery.
[0113] In this embodiment, the pore volume of the base material 11 is in the range of 0.6 cm 3 / g~2.0cm 3 / g.
[0114] For example, the pore volume of the substrate material 11 may be 0.6 cm 3 / g, 1cm 3 / g, 1.4cm 3 / g, 1.8cm 3 / g or 2cm 3 / g, etc. There is no limit here.
[0115] Preferably, the pore volume of the substrate material 11 is in the range of 0.8 cm 3 / g~2.0cm 3 / g; More preferably, the pore volume of the base material 11 is in the range of 0.8cm 3 / g~1.8cm 3 / g.
[0116] It can be understood that when the pore volume of the substrate material 11 is low (e.g., less than 0.6 cm 3 ), the negative electrode active material cannot deposit enough lithium, resulting in a decrease in the energy density of the negative electrode active material; when the pore volume of the substrate material 11 is high (for example, greater than 2cm 3 ), the structural stability of the base material 11 is poor and the compaction density is low. The pore volume range of the base material 11 is 0.6 cm 3 / g to 2.0cm 3 The setting of / g can make the pore volume of the base material 11 within an appropriate range. On the basis of ensuring the structural stability of the base material 11, the base material 11 can have a relatively large pore space, so that there is more space inside the negative electrode active material to accommodate lithium ions, which can improve the lithium storage capacity of the negative electrode material, thereby increasing the energy density of the battery; it can also provide sufficient buffer space for the volume change of the negative electrode active material during the charge and discharge process, reduce the stress concentration inside the material, maintain the integrity of the negative electrode structure, and thus improve the cycle stability of the battery.
[0117] In this embodiment, the average pore diameter of the pores of the base material 11 is in the range of 2.0 nm to 10.0 nm.
[0118] For example, the average pore size of the pores of the base material 11 may be 2.0 nm, 4.0 nm, 6.0 nm, 8.0 nm or 10.0 nm, etc., which is not limited here.
[0119] It can be understood that the above-mentioned setting is conducive to the first material 12 (such as silicon nanoparticles) entering the pores and adhering to the inner walls of the pores to form a stable composite structure, thereby improving the stability of the composite core material 10; at the same time, it also improves the process feasibility of preparing the composite core material 10.
[0120] In this embodiment, the volume proportion of the mesopores in the pores of the base material 11 is greater than 60%.
[0121] For example, the volume proportion of the mesopores in the pores of the base material 11 may be 60%, 65%, 70%, 75% or 80%, etc., which is not limited here.
[0122] It can be understood that the pore size of the mesopores is between 2nm and 50nm. The above setting can make it easier for the first material 12 (for example, silicon nanoparticles with a particle size less than 5nm) to enter the pores and adhere to the inner walls of the pores to form a stable composite structure, thereby improving the stability of the composite core material 10; at the same time, it also improves the process feasibility of preparing the composite core material 10.
[0123] In this embodiment, the coating material 20 includes fluorocarbon.
[0124] Understandably, fluorocarbons react during the first cycle of a lithium-ion battery: CF x +xLi→C+xLiF, the potential for lithium (vs.Li+ / Li) of this reaction is significantly higher than that of the base material 11 and the first material 12, so after the negative electrode active material is assembled into a lithium-ion battery, the fluorocarbon compound will preferentially react with lithium at a high potential. - Can and Li + The combined LiF has a higher interfacial energy (LiF / Li0.77J / cm 2 ), which can inhibit the deposition of lithium metal on the outer surface of the negative electrode active material and avoid the generation of lithium dendrites. In addition, the fluorocarbon compound can isolate the lithium deposited in the pores of the base material 11 from the electrolyte / electrolyte, which can greatly reduce the probability of side reactions between the metal lithium and the electrolyte / electrolyte, and further improve the cycle performance.
[0125] In this embodiment, the ratio of the molar number of the fluorine element to the molar number of the carbon element in the coating material 20 is greater than 0 and less than or equal to 1.
[0126] For example, the ratio of the molar number of the fluorine element to the molar number of the carbon element in the coating material 20 may be 0.2, 0.4, 0.8 or 1, etc., which is not limited here.
[0127] It can be understood that when the ratio of the molar number of fluorine element to the molar number of carbon element in the coating material 20 is greater than 1, the fluorine content in the coating material 20 is greater than the carbon content. Although a denser LiF interface layer can be formed, more Li will be consumed during the first lithium insertion. + , resulting in a decrease in the first coulombic efficiency of the negative electrode active material. At the same time, excessive F doping will lead to an increase in the number of perfluorinated groups, a decrease in the conductivity of the fluorocarbon layer after lithiation, and an increase in ohmic polarization, showing poor electrochemical performance. Therefore, through the above settings, the first coulombic efficiency of the battery can be improved, and the electrochemical performance of the negative electrode active material can be improved.
[0128] In this embodiment, the coating material 20 includes an inner layer material 21 and an outer layer material 22. The inner layer material 21 is composed of carbon elements, and the outer layer material 22 is composed of fluorocarbon compounds.
[0129] It can be understood that when the inner layer material 21 of the coating material 20 contains fluorine, the fluorine may react with the silicon nanoparticles in the base material 11 to generate fluoride, which will reduce the lithium affinity of the silicon nanoparticles after lithiation. Therefore, the above setting can ensure the lithium affinity of the first material 12.
[0130] In this embodiment, the content of fluorine element in the outer layer material 22 gradually increases along the direction away from the composite core material 10 .
[0131] It can be understood that the outer layer material 22 is located on the side closer to the electrolyte, so that more fluorine elements can react with lithium to form a thicker and more stable LiF layer, thereby more effectively protecting the composite core material 10; and, the reaction product of fluorine elements and lithium, LiF, has a higher interfacial energy, which can enhance the interface stability between the material and the electrolyte. As the fluorine content of the outer layer material 22 gradually increases, the interface stability of the outer layer material 22 may also be further improved, which helps to reduce the performance degradation of the battery during the charging and discharging process and improve the cycle life and safety of the battery.
[0132] In this embodiment, in the X-ray photoelectron spectrum of the outer layer material 22, the peak position of the C1s electron binding energy ranges from 283.3 eV to 288.6 eV, and the peak position of the F1s electron binding energy ranges from 684 eV to 694 eV.
[0133] It can be understood that when the peak position of the C1s electron binding energy is in the range of 283.3eV to 288.6eV, the carbon atom forms a covalent bond with the fluorine element with a stronger electronegativity, which reduces the electron cloud density of the carbon atom and increases the binding energy. When the peak position of the F1s electron binding energy is in the range of 684eV to 694eV, the fluorine atom forms a CF bond with the carbon atom. Therefore, when the X-ray photoelectron energy spectrum of the outer layer material 22 meets the above conditions, the outer layer material 22 forms a relatively stable fluorocarbon compound layer.
[0134] In this embodiment, the mass proportion of the coating material 20 in the negative electrode active material is in the range of 2% to 12%.
[0135] For example, the mass proportion of the coating material 20 in the negative electrode active material may be 2%, 4%, 6%, 8%, 10% or 12%, etc., which is not limited here.
[0136] It can be understood that through the above-mentioned setting, a thicker and more stable LiF layer can be formed on the coating material 20, thereby more effectively protecting the composite core material 10, effectively inhibiting the formation of lithium dendrites and the uniform deposition of lithium, and effectively improving the performance of the negative electrode active material.
[0137] In this embodiment, the Dv50 of the negative electrode active material is in the range of 4 μm to 25 μm.
[0138] Illustratively, the Dv50 of the negative electrode active material may be 4 μm, 10 μm, 15 μm, 20 μm, or 25 μm, etc., which is not limited herein.
[0139] It can be understood that when the Dv50 range of the negative electrode active material is 4μm to 25μm, the particles with a particle size in the range of 4μm to 25μm account for 50% of the negative electrode active material. The particle size of the negative electrode active material particles is within a suitable range, which can optimize the compaction density of the negative electrode active material, improve the transmission efficiency of lithium ions, reduce internal resistance, and thus improve the cycle stability and service life of the battery.
[0140] In this embodiment, the specific surface area of the negative electrode active material is in the range of 1.0 m 2 / g~4.5m 2 / g.
[0141] For example, the specific surface area of the negative electrode active material may be 1.0 m 2 / g, 2.0m 2 / g, 3.0m 2 / g, 3.5m 2 / g or 4.5m 2 / g, etc. There is no limit here.
[0142] It can be understood that the above arrangement can provide more lithium ion diffusion channels, which is conducive to the rapid insertion and extraction of lithium ions, thereby improving the electrochemical performance of the battery.
[0143] This embodiment provides a method for preparing a negative electrode active material. Figure 2 As shown, the preparation method of the negative electrode active material includes: S1-S2.
[0144] S1: forming a composite core material 10 ; the composite core material 10 comprises a base material 11 and a first material 12 , the base material 11 has a plurality of pores, and the first material 12 is arranged on the pore walls of the pores of the base material 11 .
[0145] S2: coating the coating material 20 on at least a portion of the outer surface of the composite core material 10 , wherein the nucleation overpotential of lithium on the first material 12 is less than the nucleation overpotential of lithium on the coating material 20 .
[0146] It can be understood that the beneficial effects that can be achieved by the method for preparing the negative electrode active material provided by the above embodiment of the present invention can refer to the beneficial effects of the negative electrode active material described above, and will not be repeated here.
[0147] In this embodiment, S1 forms the composite core material 10 , including: using a vapor deposition process and silicon source gas to form a first material 12 on the pore walls of the base material 11 .
[0148] Exemplarily, the silicon source gas includes at least one of tetrahydrosilane, disilane, tetrafluorosilane, silicon trichloride, chlorosilane, hexamethyldisilane, tris(trimethylsilyl)silane, methylvinyldichlorosilane, dimethylvinylchlorosilane, tetravinylsilane, and vinyltrichlorosilane.
[0149] It can be understood that the silicon source gas is a precursor that provides silicon elements, which will decompose or react with other gases at high temperatures to generate silicon nanoparticles, and deposit on the pore walls of the base material 11 to form the desired first material 12. In the case where the silicon source gas includes the above-mentioned silicon compound, only a small amount of silicon source gas is needed to form silicon nanoparticles, which greatly reduces the silicon loading required for the deposition process, can significantly reduce the vapor deposition reaction time, and reduce material costs.
[0150] In this embodiment, in the vapor deposition process of S1 to form the composite core material 10, the deposition temperature ranges from 400°C to 1000°C.
[0151] Illustratively, the deposition temperature may be 400° C., 600° C., 800° C., or 1000° C., etc., but is not limited thereto.
[0152] It can be understood that, through the above arrangement, silicon nanoparticles with smaller particle sizes can be generated, and the interaction between the base material 11 and the silicon source gas can be enhanced, so that the silicon nanoparticles are more evenly deposited on the pore walls of the base material 11.
[0153] In this embodiment, S2 is coating the coating material 20 on at least a portion of the outer surface of the composite core material 10, including: step (1) to step (2).
[0154] Step (1): using a vapor deposition process and a carbon source gas to form a carbon coating material on at least a portion of the outer surface of the composite core material 10.
[0155] Step (2): fluorination treatment of the carbon-coated material is performed using a fluorine-containing gas.
[0156] In some examples, through the above-mentioned fluorination treatment, the carbon coating material is converted into an outer layer material 22 and an inner layer material 21 , wherein the outer layer material 22 includes a fluorocarbon compound and the inner layer material 21 includes carbon.
[0157] Exemplarily, the carbon source gas includes a hydrocarbon material, and the hydrocarbon material includes at least one of methane, acetylene, propylene, propane, toluene, xylene, and styrene.
[0158] Illustratively, the fluorine-containing gas includes at least one of fluorine gas, nitrogen trifluoride, and chlorine trifluoride.
[0159] It can be understood that in this step, a carbon source gas is used as a precursor to form a carbon coating material on at least part of the outer surface of the composite core material 10 through a vapor deposition process. After the carbon coating material is formed, a fluorine-containing gas is used to perform a fluorination treatment to obtain a fluorinated carbon coating material.
[0160] In this embodiment, in the vapor deposition process for forming the carbon coating material, the deposition temperature ranges from 550°C to 1000°C.
[0161] Illustratively, the deposition temperature may be 550° C., 700° C., 800° C., 900° C., or 1000° C., etc., but is not limited thereto.
[0162] It can be understood that the above arrangement can form a relatively uniform carbon layer (the material of which is a carbon coating material) on at least a portion of the outer surface of the composite core material 10 .
[0163] In this embodiment, the treatment temperature of the fluorination treatment of the carbon coating material ranges from 100°C to 600°C.
[0164] For example, the treatment temperature of the fluorination treatment of the carbon coating material may be 100° C., 200° C., 300° C., 500° C., or 600° C., etc., which is not limited here.
[0165] It can be understood that the above arrangement can form a fluorinated carbon coating material with a relatively uniform thickness on the carbon coating material.
[0166] It should be noted that the mass percentage of silicon nanoparticles, the mass percentage of the fluorocarbon compound layer, and the molar number of carbon elements in the fluorocarbon compound layer in the embodiment of the present invention can be controlled by the amount of silane, carbon source, and fluorine-containing gas introduced. For example, during fluorination, the amount of fluorine-containing gas is adjusted by adjusting the flow rate of the fluorine-containing gas within a fixed time, or, at a fixed flow rate, the amount of fluorine-containing gas is adjusted by adjusting the introduction time of the fluorine-containing gas.
[0167] The chemical vapor deposition of the carbon source gas in the embodiment of the present invention can be a conventional CVD process in industry; the deposition chamber used is any one of a fluidized bed, a tubular furnace, a rotary kiln (rotary kiln), a push plate kiln, a roller kiln, a conveyor belt kiln, an air cushion kiln or a walking beam heating furnace. The protective gas introduced is generally at least one of argon and nitrogen.
[0168] The technical solution of the present invention is further described below by specific embodiments. Those skilled in the art should understand that the embodiments are only to help understand the present invention and should not be regarded as specific limitations of the present invention. The known elements of the present invention may not be described in detail or may be omitted so as not to hinder the understanding of other more relevant details.
[0169] Example 1
[0170] Example 1 provides a negative electrode active material, and the preparation method is as follows:
[0171] Step 1: Provide a carbon substrate material, specifically: commercially available, with a D50 of 8.1 μm and a specific surface area of 1847 m 2 / g, pore volume is 1.6cm 3 / g, with an average pore size of 3.46nm; then silicon is deposited in the pores of the carbon base material at a deposition temperature of 570°C, so that the mass proportion of silicon nanoparticles in the negative electrode active material is 10%; a composite core material 10 is formed.
[0172] Step 2: An amorphous carbon layer is coated on the outer surface of the composite core material 10, and the mass proportion of the amorphous carbon layer in the negative electrode active material is 4%; then, the amorphous carbon coating layer is fluorinated with fluorine gas at 150°C so that the ratio of the molar number of fluorine element to the molar number of carbon element is 0.3, thereby forming a negative electrode active material.
[0173] Example 2
[0174] Example 2 provides a negative electrode active material, and the preparation method is the same as that of Example 1, except that the mass proportion of silicon nanoparticles in the negative electrode active material is 5%.
[0175] Example 3
[0176] Example 3 provides a negative electrode active material, and the preparation method is the same as that of Example 1, except that the mass proportion of silicon nanoparticles in the negative electrode active material is 20%.
[0177] Example 4
[0178] Example 4 provides a negative electrode active material, and the preparation method is the same as that of Example 1, except that the amorphous carbon coating layer is fluorinated so that the ratio of the molar number of fluorine element to the molar number of carbon element is 0.05.
[0179] Example 5
[0180] Example 5 provides a negative electrode active material, and the preparation method is the same as that of Example 1, except that the amorphous carbon coating layer is fluorinated so that the ratio of the number of moles of fluorine element to the number of moles of carbon element is 0.8.
[0181] Example 6
[0182] Example 6 provides a negative electrode active material, and the preparation method is the same as that of Example 1, except that the mass proportion of silicon nanoparticles in the negative electrode active material is 50%.
[0183] Example 7
[0184] Example 7 provides a negative electrode active material, and the preparation method is the same as that of Example 1, except that the amorphous carbon coating layer is fluorinated so that the ratio of the molar number of fluorine element to the molar number of carbon element is 3.
[0185] Comparative Example 1
[0186] Comparative Example 1 provides a negative electrode active material, and the preparation method is the same as that of Example 1, except that silicon nanoparticles are not deposited in the pores of the carbon base material.
[0187] Comparative Example 2
[0188] Comparative Example 2 provides a negative electrode active material, and the preparation method is the same as that of Example 1, except that the amorphous carbon coating layer is not subjected to fluorination treatment.
[0189] Performance Testing
[0190] The negative electrode active materials of the above-mentioned embodiments and comparative examples were mixed with conductive carbon black and lithium polyacrylate to prepare the negative electrode sheet. The positive electrode sheet was prepared by mixing the ternary NCM811 positive electrode with a conductive agent and polyvinylidene fluoride. The positive electrode sheet, the negative electrode sheet, and 1M LiPF6 EC / DEC / FEC electrolyte (volume ratio 70 / 20 / 10) were used to assemble a 2032 button-type full battery, and the cycle performance was evaluated at 0.33C. Among them, the negative electrode coating weight was controlled to be 3mg / cm 2 , the positive electrode coating weight is 17mg / cm 2 , the results are shown in Table 1.
[0191] Table 1 Performance parameters of negative electrode active materials
[0192] First coulombic efficiency Average discharge voltage 50-cycle capacity retention rate Example 1 84.70% 3.53V 92% Example 2 84.50% 3.55V 87% Example 3 84.70% 3.44V 90% Example 4 86.00% 3.53V 82% Example 5 82.30% 3.53V 89% Example 6 84.70% 3.32V 80% Example 7 75.50% 3.53V 85% Comparative Example 1 84.10% 3.56V 66% Comparative Example 2 85.90% 3.53V 82%
[0193] From Table 1, by comparing Example 1 and Comparative Example 1, it can be seen that the carbon substrate material of Comparative Example 1 does not deposit silicon nanoparticles, resulting in fewer lithium-philic active sites, and the cycle capacity retention rate of Comparative Example 1 is significantly lower than that of Example 1. It can be seen that the addition of lithium-philic substances has a significant impact on the cycle life. That is, too low silicon content leads to fewer lithium-philic active sites, resulting in insufficient improvement of lithium deposition uniformity and dendrites, and poor cycle performance.
[0194] From Table 1, by comparing Example 1 and Comparative Example 2, it can be seen that the negative electrode active material of Comparative Example 2 does not perform fluorination treatment on the amorphous carbon coating layer, but when the degree of fluorination of the negative electrode active material of Comparative Example 2 is low, the surface lithium repellency of the negative electrode active material is insufficient, resulting in the growth of lithium dendrites, and the cycle capacity retention rate of Comparative Example 2 is greatly reduced compared with that of Example 1, and the cycle performance is poor. It can be seen that if the surface lithium repellency treatment is not performed, lithium is easily precipitated on the surface of the composite material particles, resulting in poor cycle performance.
[0195] As shown in Table 1, the first coulombic efficiency of the negative electrode active material is mainly related to the ratio of the molar number of fluorine element to the molar number of carbon element in the fluorocarbon compound. The ratio of the molar number of fluorine element to the molar number of carbon element in the fluorocarbon compound of Example 4 and Example 5 is in the range of 0 to 1, and the ratio of the molar number of fluorine element to the molar number of carbon element in the fluorocarbon compound of Example 7 is 3, that is, the degree of fluorination of the negative electrode active material of Example 7 is increased, so that the first coulombic efficiency and cycle capacity retention rate of the negative electrode active material of Example 7 are greatly reduced compared with those of Example 1. It can be seen that the coating layer is over-fluorinated, and the active Li consumed during the first lithium insertion +The fluorination rate also increases, resulting in reversible lithium ion consumption and low first coulombic efficiency. At the same time, excessive fluorination will lead to low electronic impedance of the coating layer, and may cause lithium-phobic fluorine silicides to form on the surface of internal silicon nanoparticles, reducing lithium-philic active sites and affecting the cycle performance of negative electrode active materials. In other words, when the ratio of the molar number of fluorine element to the molar number of carbon element in the fluorocarbon compound is greater than 0 and less than or equal to 1, the first coulombic efficiency and cycle performance of the negative electrode active material can be improved.
[0196] The mass proportion of silicon nanoparticles in the negative electrode active materials of Examples 1 to 3 is 5% to 20%, and the mass proportion of silicon nanoparticles in the negative electrode active materials of Example 6 is 50%. The average discharge voltage and cycle capacity retention rate of Example 6 are significantly lower than those of Example 1, that is, too high silicon content may increase the stress between silicon particles after lithiation, affect its lithium affinity effect, and deteriorate the cycle performance of the negative electrode active material. It can be seen that after the silicon deposition amount is further increased, the remaining pore space is small, the stress between particles increases after lithium insertion, and the lithium affinity effect is lost. Lithium is mainly stored in the form of alloys, and the average voltage is Li 15 The characteristics of Si4. At the same time, pure silicon-carbon materials expand too much, causing the particles to break or lose contact with the conductive network, resulting in poor cycle performance. In other words, the mass proportion of silicon nanoparticles in the negative electrode active material is 5% to 20%, which can improve the cycle performance of the negative electrode active material.
[0197] The above embodiments are only preferred embodiments for fully illustrating the present invention, and the protection scope of the present invention is not limited thereto. Any equivalent substitution or change made by a person skilled in the art based on the present invention is within the protection scope of the present invention.
Claims
1. A negative electrode active material, characterized in that: include: A composite core material, the composite core material comprising a base material and a first material, the base material having a plurality of pores, the first material being arranged on the pore walls of the pores of the base material; A coating material, coating at least a portion of the outer surface of the composite core material; The nucleation overpotential of lithium on the first material is less than the nucleation overpotential of lithium on the coating material.
2. The negative electrode active material according to claim 1, characterized in that The particle size of the first material is smaller than the pore size of the base material, and the composite core material has a porous structure.
3. The negative electrode active material according to claim 1, characterized in that The first material includes silicon nanoparticles.
4. The negative electrode active material according to claim 3, characterized in that The particle size of the silicon nanoparticles is less than or equal to 5 nm.
5. The negative electrode active material according to claim 3, characterized in that: The silicon nanoparticles are amorphous silicon nanoparticles.
6. The negative electrode active material according to claim 5, characterized in that In the Raman spectrum of the amorphous silicon nanoparticles, at 400 cm -1 ~600cm -1 In the range, the characteristic peak of amorphous silicon is 480cm -1 The integrated area accounts for greater than or equal to 90%.
7. The negative electrode active material according to claim 1, characterized in that The mass proportion of the first material in the negative electrode active material is in the range of 5% to 20%.
8. The negative electrode active material according to claim 1, characterized in that The volume proportion of the first material in the negative electrode active material is in the range of 10% to 20%.
9. The negative electrode active material according to claim 1, characterized in that: The base material includes a carbon base material.
10. The negative electrode active material according to claim 1, characterized in that The surface area of the substrate material ranges from 800 m 2 / g~2500m 2 / g; and / or, The pore volume of the substrate material ranges from 0.6 cm 3 / g~2.0cm 3 / g.
11. The negative electrode active material according to claim 1, characterized in that: The average pore size of the pores of the base material is in the range of 2.0 nm to 10.0 nm; and / or, The volume proportion of mesopores in the pores of the base material is greater than 60%.
12. The negative electrode active material according to any one of claims 1 to 11, characterized in that The coating material includes a fluorocarbon compound.
13. The negative electrode active material according to claim 12, characterized in that: The ratio of the molar number of the fluorine element to the molar number of the carbon element in the coating material is greater than 0 and less than or equal to 1.
14. The negative electrode active material according to claim 12, characterized in that: The coating material comprises an inner layer material and an outer layer material, wherein the inner layer material is composed of carbon elements, and the outer layer material is composed of fluorocarbon compounds.
15. The negative electrode active material according to claim 14, characterized in that: The fluorine content of the outer layer material gradually increases in a direction away from the composite core material.
16. The negative electrode active material according to claim 15, characterized in that: In the X-ray photoelectron spectrum of the outer layer material, the peak position of the C1s electron binding energy ranges from 283.3 eV to 288.6 eV, and the peak position of the F1s electron binding energy ranges from 684 eV to 694 eV.
17. The negative electrode active material according to any one of claims 1 to 10, characterized in that The coating material accounts for 2% to 12% by mass of the negative electrode active material.
18. The negative electrode active material according to any one of claims 1 to 10, characterized in that The Dv50 of the negative electrode active material is in the range of 4 μm to 25 μm.
19. The negative electrode active material according to any one of claims 1 to 10, characterized in that The specific surface area of the negative electrode active material is in the range of 1.0 m 2 / g~4.5m 2 / g.
20. A method for preparing a negative electrode active material, characterized in that: include: Forming a composite core material; the composite core material comprises a base material and a first material, the base material has a plurality of pores, and the first material is arranged on the pore walls of the pores of the base material; The coating material is coated on at least a portion of the outer surface of the composite core material; wherein the nucleation overpotential of lithium on the first material is less than the nucleation overpotential of lithium on the coating material.
21. The method for preparing a negative electrode active material according to claim 20, characterized in that: The forming of the composite core material comprises: adopting a vapor deposition process and using silicon source gas to form a first material on the pore walls of the pores of the base material.
22. The method for preparing the negative electrode active material according to claim 21, characterized in that: In the vapor deposition process for forming the composite core material, the deposition temperature ranges from 400°C to 1000°C.
23. The method for preparing a negative electrode active material according to claim 21, characterized in that: The silicon source gas includes at least one of tetrahydrosilane, disilane, tetrafluorosilane, silicon trichloride, chlorosilane, hexamethyldisilane, tris(trimethylsilyl)silane, methylvinyldichlorosilane, dimethylvinylchlorosilane, tetravinylsilane and vinyltrichlorosilane.
24. The method for preparing a negative electrode active material according to any one of claims 20 to 23, characterized in that: The step of coating the coating material on at least a portion of the outer surface of the composite core material comprises: A vapor deposition process is adopted to form a carbon coating material on at least a portion of the outer surface of the composite core material using a carbon source gas; and a fluorine-containing gas is used to perform a fluorination treatment on the carbon coating material.
25. The method for preparing a negative electrode active material according to claim 24, characterized in that: The carbon source gas includes a hydrocarbon material, and the hydrocarbon material includes at least one of methane, acetylene, propylene, propane, toluene, xylene and styrene.
26. The method for preparing a negative electrode active material according to claim 24, characterized in that: In the vapor deposition process for forming the carbon coating material, the deposition temperature ranges from 550°C to 1000°C.
27. The method for preparing a negative electrode active material according to claim 24, characterized in that: The fluorine-containing gas includes at least one of fluorine gas, nitrogen trifluoride and chlorine trifluoride.
28. The method for preparing a negative electrode active material according to claim 24, characterized in that: The treatment temperature of the fluorination treatment of the carbon coating material is in the range of 100°C to 600°C.
29. A negative electrode plate, characterized in that: include: current collector; A negative electrode material layer is provided on at least one surface of the current collector, and the material of the negative electrode material layer includes the negative electrode active material according to any one of claims 1 to 19.
30. A lithium ion battery, characterized in that: include: An electrolyte, a positive electrode sheet and a negative electrode sheet as claimed in claim 29; The positive electrode sheet and the negative electrode sheet are arranged in the electrolyte.
Citation Information
Cited By
Shape memory alloy-based negative electrode material, preparation method thereof and all-solid-state battery
CN121565841A
Negative electrode active material and preparation method therefor, negative electrode sheet, and lithium ion battery
WO2026157297A1